Analysis of the Main Character's Resistance to Racism in Theodore Melfi's Hidden Figures Film - Muthmainnah, Muthmainnah; Marzuki, Abdul Gafur; Erizar, Erizar; Ulinsa, Ulinsa; Harmisa, Harmisa; Azis, Sulihin; B, M. Asri (Universitas Cokroaminoto Palopo, 2024)
This study aims to describe the main character's resistance to racism in Theodore Melfi's film Hidden Figures. This research is a qualitative descriptive study, as a research procedure that can produce descriptive data that can be in the form of written or spoken words from people with observable behavior. Qualitative descriptive research aims to make a systematic, factual, and accurate description, description, or painting of facts and characteristics, as well as the relationship between things being investigated. The techniques in data analysis used in this study are 1) data reduction, 2) data presentation, and 3) verification. The results obtained describe the existence of racial discrimination and the attitudes of the main character of the film Hidden Figures' resistance to discrimination which is divided into 6 parts, namely: 1) Racial Justification, 2) Classification Based on Skin Color in Place Settings, 3) Racism in Facilities General Black/Skin, 4) Unpleasant Treatment and, 5) Promote Equality.